2023
DOI: 10.1186/s12877-023-03829-x
|View full text |Cite
|
Sign up to set email alerts
|

Job demands and resources as drivers of exhaustion and leaving intentions: a prospective analysis with geriatric nurses

Abstract: Background Nurses show a high prevalence of exhaustion and increased leaving intentions. With this study, we integrate established research about turnover intention with recent burnout literature and present a theoretical model that combines both. The aim of this study was to examine job demands (time pressure, social conflicts) and resources (job control, supervisor support, task identity, person-organisation fit) as drivers and health and age as moderators for the relationships between exhaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 64 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Meanwhile, the motivation to acquire resources will be triggered, leading to their TI [ 9 ]. Previous research has shown that job demands and resources are directly related to TI and can indirectly contribute to TI through exhaustion and depersonalization [ 10 , 11 ]. In addition, lack of resources reinforces the relationship between job demands and exhaustion [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the motivation to acquire resources will be triggered, leading to their TI [ 9 ]. Previous research has shown that job demands and resources are directly related to TI and can indirectly contribute to TI through exhaustion and depersonalization [ 10 , 11 ]. In addition, lack of resources reinforces the relationship between job demands and exhaustion [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that job demands and resources are directly related to TI and can indirectly contribute to TI through exhaustion and depersonalization [ 10 , 11 ]. In addition, lack of resources reinforces the relationship between job demands and exhaustion [ 10 ]. Studies have emphasized the versatility and flexibility of the JD-R model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies indicate gender differences in leadership behavior ( Shen and Joseph 2021 ), gender differences in work conditions for teleworking managers seems to be a rather sparsely researched area, where a few studies have investigated gender specific perceptions of work conditions in relation to family conditions and mental health outcomes [see Xie et al (2021) and Rahnfeld et al (2023) ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, women have been shown to be more affected by job demands and psychological distress and perceive job demands as job-family demands and job support as job-family support ( Banerjee and Doshi, 2020 ; Xie et al, 2021 ). Also, for females, job demands predict work–family conflicts and exhaustion and work–family conflict predicts lack of well-being ( Akram, 2020 ; Gu et al, 2020 ; Rahnfeld et al, 2023 ). Other studies have shown mixed results regarding gender differences in the association between JDCS variables, work–family conflict and well-being.…”
Section: Introductionmentioning
confidence: 99%